Analysis of Greenhouse Gas Emission Calculations Based on the Corrected IPCC Method at Coal-fired Power Plant - Tuwaluyo, Edward Putra; Slamet, S. (Jurnal Rekayasa Kimia & Lingkungan, 2025)
Greenhouse gas (GHG) emissions from coal-fired power plants, including carbon dioxide (CO), methane (CH), and nitrous oxide (NO), significantly contribute to climate change. The 2300 MW coal-fired power plant (PLTU) in Java, Indonesia, plays a key role in national energy supply but also generates substantial emissions. This study conducts GHG inventory and emissions analysis using the corrected IPCC method (Tier-1, Tier-2, and Tier-3) and evaluates mitigation strategies in fuel usage, waste management, and transportation. The IPCC methodology categorizes Tier-1 as using default emission factors, Tier-2 incorporating country-specific factors, and Tier-3 using direct measurements and real-time data. Meanwhile, Method-1, Method-2, and Method-3 reflect different correction levels for emission factors and fuel oxidation, with Method-3 (Tier-3) being the most accurate. Total GHG emissions from 20212023 reached 14,413,328 tons COe, with fuel usage as the dominant contributor (14,413,302 tons COe). Method-3 Tier-3 resulted in 11,006,815 tons COe, 11.89% lower than Methode-2 Tier-2 (11,018,851.21 tons COe) and Method-1 Tier-1 (12,492,384 tons COe). High-calorific coal (4,397 Kcal/kg) reduced emissions per energy unit, while biomass co-firing (2.7% in 2023) requires expansion for further reductions. Biodiesel is more effective than CN48 diesel in cutting emissions, aligning with its carbon-neutral classification in the 2018 ESDM GHG Inventory Guidelines. This study recommends optimizing coal calorific value, increasing biomass co-firing, and transitioning to biodiesel to reduce GHG emissions in coal-fired power plants, supporting carbon trading and national mitigation policies.